Opioid Use, Mortality Risks and Crime: Insights from a Rapid Reduction in Heroin Supply - Moore, Timothy J.; Schnepel, Kevin T. (The Review of Economics and Statistics, 2026)
Abstract In 2001 a large and sustained supply shock halted a heroin epidemic in Australia. We use drug offenses to identify individual opioid users and examine how the shock affected their mortality risks and criminal activity over the next eight years. Initially, gains from fewer overdoses are offset by drug substitution and more crime, including homicides. Most adverse effects dissipate over time, whereas persistent mortality reductions save the lives of around one in 48 individuals in our sample. Our results demonstrate that reducing the supply of illicit opioids can lead to meaningful longer-term improvements, even when the short-term effects are ambiguous.